2018
DOI: 10.1590/0001-3765201820180310
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemistry, microbiology, fatty acids composition and volatile profile of traditional Söğle tulum (goat’s skin bag) cheese

Abstract: Söğle cheese is a type of traditional tulum (goat's skin bag) cheese produced from goat's milk or a mixture of goat's and sheep's milk in Küçük Söğle and Büyük Söğle villages, Antalya, Turkey. This is the first study that aimed to investigate the physicochemistry, microbiology, fatty acids composition and volatile profile of traditional Söğle cheeses ripened in goat's skins for three months in wells. The pH and titratable acidity values, total solids, fat, protein and salt contents of the Söğle cheese samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Tulum cheese is one of the traditional cheeses, usually made from raw sheep milk in Turkey (Tekin & Guler, 2019). Also made from goat's milk, combination of sheep's and goat's milk, or cow's milk (Gürsoy, Küçükçetin, Gökçe, Ergin, & Kocatürk, 2018). Ripening is mostly done in a plastic barrel or goat skin bag (Tekin & Guler, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tulum cheese is one of the traditional cheeses, usually made from raw sheep milk in Turkey (Tekin & Guler, 2019). Also made from goat's milk, combination of sheep's and goat's milk, or cow's milk (Gürsoy, Küçükçetin, Gökçe, Ergin, & Kocatürk, 2018). Ripening is mostly done in a plastic barrel or goat skin bag (Tekin & Guler, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…, Medjoudj et al (2017a) andGursoy et al (2018) found that ethyl esters are the most abundant esters in Divle Cave, Bouhezza and Söğle Tulum cheese, respectively. Ethyl acetate and ethyl octanoate amounts increase in the first stage of ripening of Divle Cave cheese, which could be related to the increase in yeasts and moulds count.…”
mentioning
confidence: 98%
“…During the ripening of low-fat probiotic Tulum cheeses, 72 volatile components were determined (Table 2a and 2b). Alcohols (5), aldehydes (8), carboxylic acids (5), esters (4), hydrocarbons (25), ketones (17), terpenes (7), and other components have been identified (1).…”
Section: Volatile Aroma Compoundsmentioning
confidence: 99%
“…Lactic acid bacteria diversity of traditional Tulum cheese ripened in goat skin (Demirci et al, 2021b), volatile aroma components (Atik et al, 2021), some properties of Erzincan Tulum cheeses produced with different probiotic cultures and materials in packaging (Akarca, 2020;Tomar et al, 2018), and the use of probiotic Enterococcus faecium and Enterococcus durum in İzmir Tulum cheese (Yerlikaya and Akbulut, 2019) have already been investigated. The microbiology, fatty acid composition, and volatile profile of traditional Sogle Tulum cheese (goat's skin bag) (Gursoy et al, 2018), some properties of low-fat Tulum cheeses (Oluk et al, 2014), and volatile aroma components of Divle Tulum cheese (Ozturkoglu-Budak et al, 2016) were also studied. However, no research has been identified on the use of inulin in the production of probiotic and low-fat Tulum cheese.…”
Section: Introductionmentioning
confidence: 99%